2 fast 2 furious - Singleton, John.; Brandt, Michael; Haas, Derek; Universal Pictures (Firm).; Magna Vision (Universal City, Calif. Universal Pictures ; distributed in the Philippines by MagnaVision, 2003)
Now an ex-cop on the run, Brian, hooks into outlaw street racing. When the Feds strong-arm him back, Brian's no rules, win-or-die skills are unleased against an international drug lord. With his velocity-addicted buddy riding shotgun, and a drop-dead-georgeous undercover agent dialing up the heat ... it becomes a desperate race for survival and justice.
Based on the characters created by Gary Scott Thompson.
Director of photography, Matthew F. Leonetti ; editors, Bruce Cannon, Dallas Puett ; music, David Arnold ; costume designer, Sanja Miklović Hays ; production designer, Keith Brian Burns.
Paul Walker, Tyrese, Eva Mendes, Cole Hauser, Chris "Ludacris" Bridges, James Remar, Thom Barry, Michael Ealy.
MPAA rating: PG-13; for street racing, violence, language, and some sensuality.
VCD
Keywords: Automobile racing -- Drama; Ex-police officers -- Drama; Drug traffic -- Drama